The Oxford handbook of borderlans of the Iberian world - Levin Rojo, Danna editora (Oxford handbooks., 2019)
This collaborative Oxford Handbook of Borderlands in the Iberian World integrates interdisciplinary approaches to illustrate the historical processes that produced borderlands in the Americas and connected them to global circuits of exchange and migration in the early modern world, extending from the fifteenth to the nineteenth-centuries. It brings together specialists in the Spanish and Portuguese imperial spheres, their geographic and cultural borderlands in both South and North America, and their maritime networks across the Caribbean, Atlantic and Pacific oceans